Lifestyle, nutritional, and health influences on consumption of artificially-sweetened beverages in educated urban populations - Nutnicha Loyfah; Aphichat Chamratrithirong; Rossarin Soottipong Gray; Umaporn Pattaravanich; Sasinee Thapsuwan; Natjera Thongcharoenchupong; Sirinya Phulkerd (PLoS ONE, 2025)
Objectives This study analysed the prevalence of artificially-sweetened beverages (ASB) consumption in the Thai population, and examined associations between ASB consumption and lifestyle, and nutritional and health-related behaviours. Study Design This study used cross-sectional design using nationally-representative data from the 2021 Health Behavior of Population Survey. Methods The study population was 8,155 Thai adults (age 20–64 years) who lived in an urban area and attained at least a bachelor degree education at the time of interview. Binary logistic regression was applied to investigate associations between ASB consumption and sociodemographic characteristics, lifestyle behaviors, and obesity in the study adults. Results The study found that participants who were overweight/obese Class 1 had 1.5 times (OR = 1.49, 95% CI 1.18–1.88) and 1.4 times (OR = 1.36, 95% CI 1.08–1.72), respectively, more likely to ASB consumption than those with normal weight. Non-smokers and those who engaged in regular physical activity were more likely to have higher ASB consumption. Participants living with one or more non-communicable disease (NCD) were more likely to be a consumer of ASB than those without a NCD (OR = 1.56, 95% CI 1.24–1.97). Some socio-demographic characteristics (e.g., sex, age, geographic area of residence, education) were also associated with ASB consumption. Conclusions The results suggest that government needs to develop effective communication strategies which convey accurate, clear, and concise information to consumers regarding the health effects of ASB consumption. This advice should be incorporated with interventions to improve food literacy, and in marketing control to improve individual consumption behavior and promote a healthier food environment.